2014
DOI: 10.1108/jhlscm-10-2012-0029
|View full text |Cite
|
Sign up to set email alerts
|

Meeting needs: value chain collaboration in stabilisation and reconstruction operations

Abstract: Purpose – From the perspective of value chains, the purpose of this paper is to analyse the organization of stabilization and reconstruction operations, most notably in Afghanistan, with the intention to improve the way the beneficiaries are involved. Design/methodology/approach – Case study: the paper first develops a theoretical framework that draws upon value chain literature. To gather empirical data fieldwork was done within the Dut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Ref. [ 16 ] developed a theoretical framework on value chains and outlined a value chain process model. To address the multi-cycle and multi-stage problem, ref.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [ 16 ] developed a theoretical framework on value chains and outlined a value chain process model. To address the multi-cycle and multi-stage problem, ref.…”
Section: Related Workmentioning
confidence: 99%
“…Many of the empirical studies have been conducted in crisis areas (Heaslip, Sharif, & Althonayan, 2012) or in (other) developing or emerging countries (Maghsoudi & Pazirandeh, 2016;Noori & Weber, 2016). For example, Rietjens, Goedee, Van Sommeren, and Soeters (2014) study supply chain collaboration in the context of Dutch reconstruction efforts in Afghanistan, and Dube, Van der Vaart, Teunter, and Van Wassenhove (2016) examine fragile host country governments' stances toward disaster assistance. Studies conducted in Western contexts center heavily around a limited number of European countries (Leiras et al, 2014;Nurmala et al, 2017).…”
Section: Interorganizational Interaction In Disaster Response Contextsmentioning
confidence: 99%
“…Another interesting result is the almost non-existent case studies of the recovery phase. Rietjens et al's (2014) study of reconstruction and Noori and Weber's (2016) study on rehabilitation are the only two identified (2.9 percent). Not surprisingly, the majority of case studies are on…”
Section: Disaster Management Phasementioning
confidence: 99%